Identification and Determination of Antibiotic Multiresistance of Gram-negative Bacteria Isolated from Hospital Sewage - Fatih Matyar (Turkish Journal of Agriculture: Food Science and Technology)
In this study it was aimed to determine the microbial diversity and level of antibiotic resistance patterns of Gram-negative bacterial isolates from the hospital sewages. The 219 Gram-negative bacterial isolates to 16 different antibiotics (belonging 10 classes), was investigated by agar diffusion method. A total of 18 species of bacteria were isolated: the most common strains isolated from all samples were Klebsiella oxytoca (27.4%), Klebsiella pneumoniae (20.5%) and Escherichia coli (20.1%). There was a high incidence of resistance to ampicillin (98.6%), streptomycin (95.9%) and erythromycin (90.0%), and a low incidence of resistance to cefepim (13.2%), imipenem (5.0%) and meropenem (3.2%). 35.6% of all bacteria isolated from hospital sewage were resistant to 9 different antibiotics. The multiple antibiotic resistances (MAR) index ranged from 0.25 to 0.94. Results show that hospital sewages have a significant proportion of antibiotic resistant Gram-negative bacteria, and these bacteria constitute a potential risk for public health.